Financial Distress Prediction of Indonesian State-Owned Construction Firms Across the COVID-19 Period Using the Altman Z-Score Method - Yuliandi, Yuliandi; Ramadhan, M. Fiqri (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
The COVID-19 pandemic, which began in early 2020, significantly disrupted global and national economies, with the construction sector in Indonesia experiencing notable contraction. This study aims to predict the financial distress of Indonesian state-owned construction companies (BUMN Karya) listed on the Indonesia Stock Exchange before (2018–2019), during (2020–2021), and after (2022–2023) the pandemic, using the Altman Z-Score model for non-manufacturing firms. Secondary data were obtained from audited annual financial statements and analyzed using descriptive quantitative methods. The findings show that, in the pre-pandemic period, most companies were in the grey zone, except Waskita Karya in 2019, which was in the distress zone. During the pandemic, most companies fell into financial distress, except PT PP, which remained in the grey zone. In the post-pandemic period, PT Adhi Karya and PT PP remained in the grey zone, while PT Wijaya Karya and PT Waskita Karya continued to be in financial distress. These results indicate that the COVID-19 pandemic worsened the financial health of BUMN Karya, with uneven recovery across firms in the subsequent years. The study offers practical implications for corporate management, policymakers, and investors in developing risk mitigation strategies for strategic infrastructure enterprises. Keywords: Altman Z-Score, financial distress, state-owned construction companies, COVID-19 pandemic, Indonesia